2021
DOI: 10.3389/fonc.2021.691798
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Detection of Circulating Tumor DNA in Extracellular Vesicles-Depleted Plasma

Abstract: Circulating tumor DNA (ctDNA) in plasma has been used as a biomarker for cancer detection and outcome prediction. In this study, we collected the five precipitates (fractions 1–5) and leftover supernatant plasma component (fraction 6) by a sequential centrifugation in plasma samples from nine small cell lung cancer (SCLC) patients. The fractions 3, 5 and 6 were large vesicles, exosomes and extracellular vesicles (EVs)-depleted plasma, respectively. Fragment size analysis using DNAs from these fractions showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, other studies reported the presence of shorter DNA fragments (152.4 bp, 160 bp) within EVs, with larger DNA fragments possibly resulting from contamination with apoptotic bodies (Sun et al., 2021 ; Zhang et al., 2019 ). The comparison between the above‐mentioned studies is difficult due to different EV isolation methods resulting in purification of various EV subtypes.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, other studies reported the presence of shorter DNA fragments (152.4 bp, 160 bp) within EVs, with larger DNA fragments possibly resulting from contamination with apoptotic bodies (Sun et al., 2021 ; Zhang et al., 2019 ). The comparison between the above‐mentioned studies is difficult due to different EV isolation methods resulting in purification of various EV subtypes.…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported that longer EV-DNA fragments may improve the detection of single nucleotide variations, copy number variations (San Lucas et al, 2016) and insertions/deletions during NGS sequencing performance and bioinformatic analysis (Waldenmaier et al, 2022). However, other studies reported the presence of shorter DNA fragments (152.4 bp, 160 bp) within EVs, with larger DNA fragments possibly resulting from contamination with apoptotic bodies (Sun et al, 2021;. The comparison between the above-mentioned studies is difficult due to different EV isolation methods resulting in purification of various EV subtypes.…”
Section:  Ev-dna Fragment Size Profilementioning
confidence: 99%
“…ctDNA fraction was estimated by FACETS from data of the WES cfDNA sample and absolute copy number (ABCN) were called depends on tumor fraction estimation from cfDNA as previously described ( 24 ), and mean tcn.em values were used. To estimate ctDNA amount, mean tcn.em values were used to calculate ctDNA content of total cfDNA ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Exosomes were isolated using the Total Exosome Isolation Kit (Invitrogen, USA) according to the manufacturer's instruction as previously described [ 21 23 ]. The serum was thawed in a 25°C water bath and then subjected to centrifugation at 2,000 × g for 30 min to remove possible residual cells debris.…”
Section: Methodsmentioning
confidence: 99%